Application of Bioavailability Models to Derive Chronic Guideline Values for Nickel in Freshwaters of Australia and New Zealand. (17th November 2020) - Stauber, Jenny; Golding, Lisa; Peters, Adam; Merrington, Graham; Adams, Merrin; Binet, Monique; Batley, Graeme; Gissi, Francesca; McKnight, Kitty; Garman, Emily; Middleton, Ellie; Gadd, Jennifer; et al.
Abstract: There has been an increased emphasis on incorporating bioavailability‐based approaches into freshwater guideline value derivations for metals in the Australian and New Zealand water quality guidelines. Four bioavailability models were compared: the existing European biotic ligand model (European Union BLM) and a softwater BLM, together with 2 newly developed multiple linear regressions (MLRs)—a trophic level‐specific MLR and a pooled MLR. Each of the 4 models was used to normalize a nickel ecotoxicity dataset (combined tropical and temperate data) to an index condition of pH 7.5, 6 mg Ca/L, 4 mg Mg/L, (i.e., approximately 30 mg CaCO3 /L hardness), and 0.5 mg DOC/L. The trophic level‐specific MLR outperformed the other 3 models, with 79% of the predicted 10% effect concentration (EC10) values within a factor of 2 of the observed EC10 values. All 4 models gave similar normalized species sensitivity distributions and similar estimates of protective concentrations (PCs). Based on the index condition water chemistry proposed as the basis of the national guideline value, a protective concentration for 95% of species (PC95) of 3 µg Ni/L was derived. This guideline value can be adjusted up and down to account for site‐specific water chemistries. Predictions of PC95 values for 20 different typical water chemistries for Australia and New Zealand varied by >40‐fold, which confirmed that correction for nickel bioavailability is critical for the derivation of site‐specific guideline values. Environ Toxicol Chem 2021;40:100–112. © 2020 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Abstract : Derivation of bioavailability‐based guidelines for nickel in freshwaters after normalization of ecotoxicity data using trophic level‐specific multiple linear regression (MLRs). SSD = species sensitivity distribution.